(untitled) (Research, Society and Development, 2021)
Introduction: Ischemic Stroke (iCVA) consists of a cerebral arterial obstruction, which results in an acute neurological lesion with important worldwide morbidity and mortality. Representing one of the main causes of hospitalization, stroke causes long-term and high-cost hospitalizations and numerous future consequences for patients, with considerable financial expense in the health system. Such mentioned aspects can be avoided when we act on several factors that influence the length of stay (LOS) of these patients. Thus, the present study aims to identify elements that influence LOS in patients who had stroke and were assisted at a neurology and neurosurgery reference institution. Methodology: This retrospective research includes all patients with cerebral infarction between 2018-2019 and the exclusion criteria were patients with neurological pathology other than stroke, under 18 years of age or with incomplete medical records. Several variables were analyzed statistically, including demographic data, risk factors, level of consciousness, affected arterial vessel and need for neurosurgery. Results: 101 patients were eligible for the study. Average age was 73 years old, with 88,1% over 60 years old. Systemic Arterial Hypertension (SAH) was present in most patients (77,23%). The majority (85,15%) presented with a Glasgow Coma Scale (GCS) greater than 8 with statistical significance in lower mortality (p=0,015) and lower LOS (p=0,001). The middle cerebral artery (MCA) was the main arterial territory affected (58,42%) and few cases required neurosurgery (4,95%). The death rate was small (11,88%). The mean LOS was 11,31 days and most patients were hospitalized for less than five days (51,48%). Conclusion: Initial presentation with a GCS scale above 8 is consistent with lower mortality and lower LOS. Understanding factors that can induce higher LOS is of paramount importance for time management, aiming at reducing the treatment expenses and optimizing skills.